Internet connectivity disruption in Bangladesh (Bangladesh) - Voidly (2026)
CRITICAL severity mixed detected in Bangladesh. Confidence: 67%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: BD-2026-0070
Keywords: censorship; BD; mixed; critical